Numerical investigation on effects of alkali metals release during combustion of char particle groups. (1st November 2020) - Qu, Sibo; You, Changfu
Abstract: Alkali metals, especially Na, are generally accepted as the primary cause of serious ash-related problems in the industrial applications of pulverized coal. This paper investigates the effects of different variables, including particle size, ambient temperature, O2 mass fraction, and atmospheres: O2 /N2 and O2 /CO2 at particle level. The fictitious domain method (FDM) provides a true direct numerical simulation (TDNS) for the investigation. Computational results show the correlation between alkali metals release and carbon consumption during char particle combustion. Here, high ambient temperature is more positive to alkali metals release than carbon consumption. In an oxygen-dominated atmosphere, a small amount of CO2 tends to form a higher temperature field than N2, which promotes a greater release of alkali metals. This paper also investigates the specific effects of volume fraction and non-uniform distribution of particles for the combustion of particle groups. The computational results show that both temperature field and alkali metals release are significantly affected by the volume fraction of particles. The effects of the non-uniform distribution of particles, e.g., uniform distribution, dense distribution on the windward side, dense distribution on the leeward side, and asymmetric distribution, on temperature field and alkali metals release vary with different volume fractions of particles. As such, the non-uniform distribution of particles plays a role in changing the mass transfer of the oxidant and the heat transfer.